Efficacy of XP-Endo Finisher R in Removing Root Filling Remnants in Root Canal Retreatment - P Amooyan; H Akhavan; E Esnaashari (Islamic Azad University, 2022)
Background and Aim: Complete removal of gutta-percha from the root canal system and its remnants is a challenge in endodontic retreatment. This ex-vivo study aimed to assess the efficacy of XP-Endo Finisher R (XEFR) in removing root filling remnants from straight canals of mandibular premolars in root canal retreatment.   Materials and Methods: In this ex-vivo study, 30 single-rooted mandibular premolars with straight roots were selected. The root canals were instrumented and filled. Retreatment was then performed using D RaCe system. Teeth were then randomized into two groups of A and B (n=15). In group A, root canal retreatment was completed with XEFR. In group B, XEFR was not used. To evaluate the filling material remnants, the roots were split into halves and assessed under a stereomicroscope and photographed. The amount of remaining gutta-percha in the coronal, middle and apical thirds of the roots was measured by AUTOCAD software and analyzed with two-way ANOVA. Results: The amount of residual filling material was significantly lower in the coronal, middle and apical thirds and the entire root length in XEFR group (P<0.001). Conclusion:  Use of XEFR signiﬁcantly decreased the residual root ﬁlling material in the root canals.